Estrategias para generar conciencia tributaria en la recaudación tributaria en las empresas industriales en la ciudad de Trujillo - periodo 2011. - Mori Yong, Milagritos Patricia (2011)
The purpose of the research is to identify strategies to raise awareness of tax on industrial enterprises in the city of Trujillo; there is the need to promote awareness among citizens about tax obligations, which is achieved with the development of culture and education programs tax, which allows for increased tax revenues from the taxpayers of our country. To improve levels of compliance is necessary for the tax supplement traditional fundraising activities, supervision and facilitation, with activities designed to promote tax consciousness and at the same time consolidate their institutional role in society. The research question was: What are the strategies to raise awareness of tax collection tax on industrial enterprises in the city of Trujillo period - 2011?. The hypothesis raised was this: The tax strategies to raise awareness is to have culture and education tax to allow the positive impact of tax collection in industrial enterprises in the city of Trujillo period - 2011. We conclude that education and culture act as tax strategies to raise awareness in industrial enterprises. According to the results it is recommended to develop information and education programs offered, promoting awareness of taxpayers, with emphasis on type, use and allocation of the proceeds of tax collection.